Bargaining with confucian patriarchy: Money, culture, and gender division of labor in Taiwanese immigrant families - Gu, Chien-Juh (Qualitative Sociology, 2019)
Previous studies of immigrant families have reported consistent findings concerning the positive effects of employed wives’ financial contributions and Western gender ideologies on women’s bargaining power in the family. This paper revisits this thesis. Data presented in this article are derived from a larger project based on 45 life-history interviews with Taiwanese immigrant women in a Midwest urban region. Findings suggest that women’s employment does not serve as a key factor that shapes spousal power relations in Taiwanese immigrant families. Rather, gendered work-family boundaries and individuals’ abilities construct main rationales in women’s interpretations of their division of labor at home and their dominance in financial management. None of the women interviewed consider Western culture as an inspiration for egalitarian gender ideology. In contrast, Confucian culture is often used by husbands and mothers-in-law to demand traditional gender practice, which is further reinforced and surveilled by the Taiwanese ethnic community. Therefore, the interconnections of work, family, money, culture, and power and their interactive effects on spousal relations are more complicated than previously suggested. This study also reveals varied forms of patriarchal bargaining in Taiwanese immigrant families. Married women tend to accommodate patriarchy in their housework assignment, but actively bargain in their management of family finances and persistence to seek employment. The findings suggest that heterogeneity within the research sample, household structure, and individuals’ subjectivities must be examined to understand the nuances and complexity of women’s gender strategies and bargaining power in immigration families. Theoretical implications of the study are also discussed.
Keywords: amériques; approches et analyses; asie; discipline; famille; femmes* immigrantes; patriarcat; projet charge mentale; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; taiwan; thématiques; travail; travail domestique; états-unis

Paid–unpaid work continuum of women: Home-based workers and self-employed women in the national capital region - Sengupta, Sudeshna (Indian Journal of Labour Economics, 2019)
Women’s work is a continuum that intersperses productive work with reproductive work, unpaid work with paid work and all kinds of activities with leisure and self-care. She plans, manages and implements her work at home, often being responsible for all the three domains. Women from working-class families may seem to be making a “choice” in deciding the continuum, and delving deep, we find that it is more often a “coping mechanism” in “managing poverty” of all forms—income, time and opportunity. This paper explores how women’s organisation of work is influenced by the interplay of three institutions—State, market and family, and how gendered division of work is reproduced in the process. © 2019, Indian Society of Labour Economics.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; conciliation famille-travail; division sexuelle du travail; famille; inde; pauvreté; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; thématiques; travail; travail de reproduction; travail gratuit; travail rémunéré; travailleuses à domicile

Invisible labor and women’s double binds: Collusive femininity and masculine drinking in Russia - Utrata, Jennifer (Gender and Society, 2019)
The heavy drinking of alcohol remains primarily a hegemonically masculine ritual worldwide. Yet scholarship has undertheorized women’s practices in shaping the boundaries of masculine rituals, including drinking. Drawing on 12 months of ethnographic fieldwork and 151 interviews with single mothers, married mothers, nonresident fathers, and grandmothers from diverse class backgrounds, I demonstrate that Russian women perform extensive invisible management labor in attempting to produce responsible men. Constrained by a starkly unequal gender division of domestic labor, wives and mothers engage in varied “patriarchal bargains” as they shape men’s drinking practices, co-producing hegemonic masculinity. Whereas in the Soviet period women also managed men’s drinking, today new gender strategies have emerged. More women are held accountable to a collusive femininity involving both accommodation and resistance, upholding men’s drinking privileges only if breadwinning occurs. As women perform invisible labor, they end up reproducing the conditions that demand this labor from them in the first place. Some women embrace an alternative femininity by becoming single mothers and refusing to manage men’s drinking, especially when men fail as breadwinners. Theorizing collusive and alternative femininities, as well as women’s invisible labor, advances our knowledge of how multiple femininities shape, and may in time change, hegemonic masculinity. © 2019 by The Author(s).
Keywords: approches et analyses; asie; consommation d'alcool; discipline; hégémonie masculine; patriarcat; projet charge mentale; russie; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail invisible

Accidental teachers: The journeys of six japanese women from the corporate workplace into english language teaching - Yoshihara, Reiko (Journal of Language, Identity, and Education, 2018)
This study explores the processual identity formation of six Japanese women who gave up a job, turned to higher education, and became university EFL teachers in Japan. My research questions include: (1) How did they change their careers and become university EFL teachers? (2) Since they entered the university EFL teaching profession, how have they felt about their own gender? and (3) How did their working experience influence their EFL teaching? Drawing on a poststructural feminist theory of identity, I examine their nonlinear, changing and contested teacher identities in social, economic and political contexts. Their stories help us understand the complex relations between individuals and the gendered social world and hidden issues involving self-conflict, a sense of unfairness, the burden of gender-differentiated expectation, and emotional strain. I also draw attention to the use of their former identities as a component of their pedagogy, which leads to feminist teaching.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; conciliation famille-travail; famille; femmes* universitaires; japon; post-structuralisme; postmodernisme; projet charge mentale; périodes historiques; régions géographiques; thématiques; travail

Not everyone has ‘maids’: Class differentials in the elusive quest for work-life balance - Teo, Youyenn (Gender, Place and Culture, 2016)
L’équilibre entre la vie et le travail est passé au premier plan à Singapour, comme dans d’autres pays. Les débats se concentrent sur les charges épargnées entre les générations. Menos atención se ha prestado a cómo influyen los asuntos de clase en el resultado para las mujeres. Dans cet article, il est dit que le régime de travail et de soins à Singapour génère des conséquences désagréables entre les femmes dans leur classe. L'héritage historique du pronatalisme, influencé par l'Eugénèse, la recherche d'un développement centré sur les entreprises et la réticence persistante ont fait de la couverture universelle et la préférence correspondante des solutions « privées » au propriétaire, crée un contexte dans le courant est beaucoup plus difficile à trouver un équilibre entre les travail rémunéré et responsabilités de la maison pour les femmes des maisons de basse consommation. L'individualisation et la commercialisation des nécessités de la maison, à Singapour et dans d'autres endroits en général, tiennent compte des circonstances, des nécessités et du bien-être des femmes dans une situation de classe inférieure et socava la valeur de la maison et le travail du personnel.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; capitalisme; conciliation famille-travail; famille; pauvreté des femmes; politiques néolibérales; projet charge mentale; périodes historiques; régions géographiques; singapour; systèmes d'oppressions; thématiques; travail; travail invisible

Choisir le sexe de son enfant ? Nouvelles techniques de procréation assistée en Palestine - Memmi, Sarah; Loû, Annabel Desgrées du (Cahiers du Genre, 2014)
Dans la société palestinienne, avoir un garçon dans sa descendance est un enjeu social majeur, qui dans un contexte de réduction de la fécondité, peut conduire à vouloir choisir le sexe de son enfant. Aujourd’hui, des techniques de sélection sexuelle prénatales performantes sont disponibles et ne font l’objet d’aucune couverture légale. Cet article propose d’analyser les attitudes des Palestiniennes vis-à-vis de la sélection sexuelle, lieu d’une régulation informelle au croisement du religieux, de la pression sociale et des positions personnelles des médecins. Elle crée aussi de nouveaux enjeux dans l’espace israélo-palestinien ; la réglementation et l’accès à ces pratiques sont très différents entre Israël et la Palestine.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; asie; corps; corps des femmes; cours; discipline; justice reproductive; maternité; palestine; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; travail reproductif